Comparison of rhenium–porphyrin dyads for CO2 photoreduction: photocatalytic studies and charge separation dynamics studied by time-resolved IR spectroscopy. Issue 12 (2nd September 2015) - Windle, Christopher D.; George, Michael W.; Perutz, Robin N.; Summers, Peter A.; Sun, Xue Zhong; Whitwood, Adrian C.
Abstract : A new dyad for photocatalytic CO2 reduction produces ten times more CO and much longer-lived charge-separation than earlier rhenium-porphyrin dyads. Abstract : We report a study of the photocatalytic reduction of CO2 to CO by zinc porphyrins covalently linked to [Re I (2, 2′-bipyridine)(CO)3 L] +/0 moieties with visible light of wavelength >520 nm.Dyad 1 contains an amide C6 H4 NHC(O) link from porphyrin to bipyridine (Bpy), Dyad 2 contains an additional methoxybenzamide within the bridge C6 H4 NHC(O)C6 H3 (OMe)NHC(O), whileDyad 3 has a saturated bridge C6 H4 NHC(O)CH2 ; each dyad is studied with either L = Br or 3-picoline. The syntheses, spectroscopic characterisation and cyclic voltammetry ofDyad 3 Br and[Dyad 3 pic]OTf are described. The photocatalytic performance of[Dyad 3 pic]OTf in DMF/triethanolamine (5 : 1) is approximately an order of magnitude better than[Dyad 1 pic]PF6 or[Dyad 2 pic]OTf in turnover frequency and turnover number, reaching a turnover number of 360. The performance of the dyads with Re–Br units is very similar to that of the dyads with [Re–pic] + units in spite of the adverse free energy of electron transfer. The dyads undergo reactions during photocatalysis: hydrogenation of the porphyrin to form chlorin and isobacteriochlorin units is detected by visible absorption spectroscopy, while IR spectroscopy reveals replacement of the axial ligand by a triethanolaminato group and insertion of CO2 into the latter to form a carbonate. Time-resolved IR spectra of[Dyad 2 pic]OTf and[Dyad 3 pic]OTf (560 nm excitation in CH2 Cl2 ) demonstrated electron transfer from porphyrin to Re(Bpy) units resulting in a shift of ν (CO) bands to low wavenumbers. The rise time of the charge-separated species for[Dyad 3 pic]OTf is longest at 8 (±1) ps and its lifetime is also the longest at 320 (±15) ps. The TRIR spectra ofDyad 1 Br andDyad 2 Br are quite different showing a mixture of 3 MLCT, IL and charge-separated excited states. In the case ofDyad 3 Br, the charge-separated state is absent altogether. The TRIR spectra emphasize the very different excited states of the bromide complexes and the picoline complexes. Thus, the similarity of the photocatalytic data for bromide and picoline dyads suggests that they share common intermediates. Most likely, these involve hydrogenation of the porphyrin and substitution of the axial ligand at rhenium.